Professor Emanuel Emeryk Machek (1852-1930): Life and Contribution to Science (Ukrainian Journal of Ophthalmology, 2026)
Galicia has been famous for its scientists in different f ields for centuries. 2017 marked the 165th anniversary of the birth of Emanuel Emeryk Machek, a distinguished professor of ophthalmology who had contributed greatly to local and international medical science. Emanuel Machek was born on March 7, 1852, in Sambir (a town near Lviv), where his father, Ivan Machek, was a bailiff. After a course at the gymnasium there, he studied at the University of Vienna, gaining his medical doctorate in 1877 [6]. He started practicing as a volunteer doctor at the Vienna Eye Clinic, where he worked under the guidance of professor Carl Ferdinand von Arlt (1812–1887), the head of the clinic, and professor Eduard Jäger (1818–1884), from 1877 to 1879.